CENTRAL RETINAL ARTERY OCCLUSION SECONDARY TO DENGUE FEVER - Sadiq, Naqaish; Naqaish, Taqdees; Arif, Abdusalam; Mohammad, Khadija; Jalis, Mubashar (Journal of Ayub Medical College Abbottabad, 2014)
Dengue fever is endemic in the tropics and subtropics and has become a worldwide health threat in recent years. Dengue-related ocular complications are increasingly being reported from countries inSouth-East Asia. The authors report the first documented case of a patient with dengue fever who developed central retinal artery occlusion in addition to many other eye complications such as severe ptosis and complete internal and external ophthalmoplegia during her convalescent phase. The disease was confirmed by specific serological tests. Despite treatment, severe visual impairment occurred in this case. Keywords: Dengue, retinal artery occlusion, vasculitis